Assessment and self-assessment: The portfolio tool and the proposal of the digital dossier - Vincenzo Nunzio Scalcione (Pensa MultiMedia, 2022)
The challenges defined by expectations, directed towards learning contexts, require the construction of paths for the integral promotion of the personality; development of identity and coexistence skills, in the post-covid globalization society, thus become central elements of reflection for scholastic institutions and teachers. Being able to keep memory of development rhythms, skills achieved and knowledge gained becomes an element capable of proposing new research paths and construction of teaching practices. The portfolio, with its ability to analyze the evaluative action, can be a tool capable of representing the complexity of the learner's training process, indicating the pupil's self-assessment, inherent in this tool, as the method of verifying the effectiveness of the devices and didactic paths proposed. In this essay we then proceed to an examination of the reference theories and tools in use for the construction of the portfolio, with the proposition of an experience made of digital dossier, with the pupils of secondary school.